Edukasi Senam Kreasi Gembira pada Anak Usia 4-6 Tahun di TK Se-Kelurahan Paguyaman Kecamatan Kota Tengah - Ruslan, Ruslan; Tumaloto, Ella H; Syam, Asry (Universitas Negeri Gorontalo, 2023)
Happy creative gymnastics is creative gymnastics that is deliberately made to develop the motor skills of students who are 4-6 years old or are in kindergarten (Kindergarten). Children's need for movement is one of the efforts to maintain children's fitness from an early age, through creative gymnastics it is hoped that it will have a positive impact on children aged 4-6 years in exploring their movement abilities. This service activity was carried out in a kindergarten located in the Paguyaman sub-district, Kota Tengah sub-district, using a training method that began with observation and continued with the practice of happy creative gymnastics with kindergarten children and teachers who became gymnastic instructors. Happy Creative Gymnastics has a positive impact on the motor skills of children aged 4-6 years who are in kindergarten. This is evidenced by the results that 54 children (55.10%) began to develop, and 24 children (24.29%) developed as expected. While children who have not developed 20 children (20.41%). So that it can be concluded that creative gymnastics can improve children's motor skills both in terms of basic movement and cognitive development of children aged 4-6 years.